Ludwig Wittgenstein and Ferdinand Ebner: Two Austrian Thinkers - Perissinotto, Luigi (Scenari, 2022)
In this paper I wonder if, and to what extent, it is possible to put a philosopher like Ludwig Wittgenstein in relation to a thinker like Ferdinand Ebner. Although there are certainly profound and obvious differences between the two, there are however many historical-biographical circumstances, as well as several cultural and philosophical aspects that justify matching the names of Wittgenstein and Ebner and render this exercise particularly instructive. In this paper I will take the following circumstances and aspects into account: their mutual offspring from the Austrian culture and society; the significance of the World War I for their life and philosophy; their common cultural and philosophical references (Kiekegaard, Kraus, Weininger, etc.); their occupation, for a certain period of time, as primary school teachers; the importance attributed to language in their philosophical thought; the refusal of any “intellectualistic” conception of philosophizing.